Frequency and Prognostic Significance of Clinical Fluctuations Before Hospital Arrival in Stroke. Issue 2 (February 2022) - Romano, Jose G.; Gardener, Hannah; Smith, Eric E.; Campo-Bustillo, Iszet; Khan, Yosef; Tai, Sofie; Riley, Nikesha; Sacco, Ralph L.; Khatri, Pooja; Alger, Heather M.; Mac Grory, Brian; Gulati, Deepak; et al.
Abstract : Background and Purpose: Clinical fluctuations in ischemic stroke symptoms are common, but fluctuations before hospital arrival have not been previously characterized. Methods: A standardized qualitative assessment of fluctuations before hospital arrival was obtained in an observational study that enrolled patients with mild ischemic stroke symptoms (National Institutes of Health Stroke Scale [NIHSS] score of 0–5) present on arrival to hospital within 4.5 hours of onset, in a subset of 100 hospitals participating in the Get With The Guidelines–Stroke quality improvement program. The number of fluctuations, direction, and the overall improvement or worsening was recorded based on reports from the patient, family, or paramedics. Baseline NIHSS on arrival and at 72 hours (or discharge if before) and final diagnosis and stroke subtype were collected. Outcomes at 90 days included the modified Rankin Scale, Barthel Index, Stroke Impact Scale 16, and European Quality of Life. Prehospital fluctuations were examined in relation to hospital NIHSS change (admission to 72 hours or discharge) and 90-day outcomes. Results: Among 1588 participants, prehospital fluctuations, consisting of improvement, worsening, or both were observed in 35.5%: 25.1% improved once, 5.3% worsened once, and 5.1% had more than 1 fluctuation. Those who improved were less likely and those who worsened were more likely to receive alteplase. Those who improved before hospital arrival had lower change in the hospital NIHSS than those who did not fluctuate. Better adjusted 90-day outcomes were noted in those with prehospital improvement compared to those without any fluctuations. Conclusions: Fluctuations in neurological symptoms and signs are common in the prehospital setting. Prehospital improvement was associated with better 90-day outcomes, controlling for admission NIHSS and alteplase treatment. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT 02072681. Abstract : Supplemental Digital Content is available in the text.